2003
DOI: 10.1046/j.1365-2656.2003.00689.x
|View full text |Cite
|
Sign up to set email alerts
|

The functional response in three species of herbivorous Anatidae: effects of sward height, body mass and bill size

Abstract: Summary1. The functional response, i.e. the quantity of food consumed per unit of time as a function of food availability, is a central process in foraging ecology. The application of this concept to foraging by mammalian herbivores has led to major insights into the process of resource acquisition, but it has so far been little used to understand foraging in avian herbivores. 2. In this study, we describe the functional responses of three grazing Anatidae, the wigeon Anas penelope L. (mean body mass in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
94
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(111 citation statements)
references
References 46 publications
(98 reference statements)
9
94
2
2
Order By: Relevance
“…This result is in line with previous findings (de Boer and Prins 1989;Prins 1996;Durant et al 2003;Si et al 2011) and our prediction. Increasing vegetation height normally results in a decrease in forage quality (van der Wal et al 2000).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This result is in line with previous findings (de Boer and Prins 1989;Prins 1996;Durant et al 2003;Si et al 2011) and our prediction. Increasing vegetation height normally results in a decrease in forage quality (van der Wal et al 2000).…”
Section: Discussionsupporting
confidence: 94%
“…Foragers face a trade-off between maximizing forage quantity and quality. Foraging theory suggests that herbivores select their habitat based on differences in body size (Gunnarsson et al 2005;Hopcraft et al 2010;Clauss et al 2013); smaller bodied species generally forage on shorter swards that contain a higher nutrient content, whereas larger species exhibit a higher intake rate and are less sensitive to variation in forage quality, and therefore select taller swards (Durant et al 2003(Durant et al , 2004Heuermann et al 2011). Hence, body size plays a pivotal role in habitat selection in relation to forage quality and quantity, and the effect of these forage variables on differences in species abundance could be used to understand the differences in spatial distribution of the species and species coexistence.…”
mentioning
confidence: 99%
“…For instance, the Taiga Bean Goose has a long thin bill adapted for probing soft substrates of bogs and marshlands to feed on underground plant material, whereas the Pink footed Goose has a short bill suitable for grazing and seed stripping (Owen, 1976;Reed, 1976). Finally, the trait utility (i.e., evidence that morphological or physiological traits are indeed useful when used in the associated environment) of beak morphology in geese has been confirmed experimentally (Durant et al, 2003;Heuermann et al, 2011;Zhang et al, 2015). The Grey Geese can thus be regarded as an adaptive radiation in terms of beak morphology.…”
Section: Biogeography and Ecologymentioning
confidence: 88%
“…For example, studies with geese have shown that animals foraged preferentially on smaller food items (Amat 1995;Durant et al 2009), and that birds may crop food items partially so that the ingested piece is smaller than the whole plant part. Beak size and morphology are correlated with bite size in birds (Cope et al 1995a,b;Durant et al 2003; Van der Graaf et al 2006), but a potential effect on fecal particle size has not been quantified yet (Durant et al 2009). Moore (1999) demonstrated that the particle size of the ingested food can affect particle breakdown in the gizzard in geese, but the effect was apparent only when food particle size was already smaller than 2 mm.…”
Section: Discussionmentioning
confidence: 99%